Método, equilíbrio, expectativas e desemprego: o debate entre keynesianos e neoclássicos - Andrada, Alexandre Flávio Silva (2008)
The present work aims to provide a critique to the Walrasian approach in Macroeconomics. The debate between Keynesians (Keynes, New Keynesians and Post-Keynesians) and Neoclassical (Monetarists and New Classical) about method, expectations, and equilibrium is presented. Trying so to refuse Lucas s critique, which says that Keynes did not respect economic analyze straightjacket , i.e., selfish agents and clear markets. About unemployment a critical revision of General Theory s second chapter is made as well the concepts of natural rate and involuntary unemployment. The conclusions are: do not seem that Friedman s instrumentalist approach is the correct referential to Macroeconomics, rational expectations hypothesis do not explain men effective behavior, continuous market clear is tautological, and involuntary unemployment referred to a foreign economic agent individual characteristics situation. It is a Macroeconomic unemployment. At last while Microeconomics can avoid historicists considerations, Macroeconomics can not. Macroeconomics issues are related to historical moment, stage of institutions development and to a more human economic agent behavior